2016
DOI: 10.1061/(asce)st.1943-541x.0001486
|View full text |Cite
|
Sign up to set email alerts
|

Application of a New System of Self-Tensioning to the Design of Large-Span Wood Floor Framings

Abstract: This study describes a self-tensioning system in which the gravitational loads acting on a horizontal structural element are automatically converted to a posttensioning force on that component. The self-tensioning effect has a variable intensity, constantly adjusted depending on the applied service loads. The selftensioning is eccentrically applied over the cross-section, and it generates a negative moment that compensates the deformations due to the gravitational loads. The system can be utilized in beams, sl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…1, α0 = 16.94°). Previous studies indicated that this configuration could display notable efficacy in transforming slight descents of the supports into a significant self-tensioning force [18].…”
Section: Test Setupmentioning
confidence: 98%
See 1 more Smart Citation
“…1, α0 = 16.94°). Previous studies indicated that this configuration could display notable efficacy in transforming slight descents of the supports into a significant self-tensioning force [18].…”
Section: Test Setupmentioning
confidence: 98%
“…This system has been patented, and it was initially developed to resolve long spans, in which post-tensioning is self-adjusting depending on the loads applied at any given time. This design has been subjected to several previous analytical studies [16][17][18], and these are now completed by an experimental study to validate its performance.…”
Section: Description Of the Systemmentioning
confidence: 99%
“…An efficient way to avoid this limitation in the pretensioning force is to apply a variable tensioning force that generates a counterbalance effect relative to the applied forces. With this goal in mind, the authors developed the SsS© (Self-stressing System) [34,35].…”
Section: Influence Of Pretensioning On the Bending Strengthmentioning
confidence: 99%
“…Prestressed concrete beams are widely used in highway and railway construction [1], and their production process consists of four steps, namely, template installation, reinforcement assembling, concrete pouring, and prestress tensioning. Prestress tensioning is an important measure to improve the tensile strength of concrete [2][3][4][5][6], and its results directly affect the performance and quality of bridges [7,8]. The development of numerical control technology and smart devices has made intelligent tensioning a mainstream technology.…”
Section: Introductionmentioning
confidence: 99%